1168 Radiotherapy Dose for HPV Driven Oropharyngeal Cancer: What Is Enough?. (12th October 2021) - Penny, F; Shanmugasundaram, R; Patel, N
Abstract: Aim: Squamous cell carcinoma of the oropharynx is associated with high-risk Human Papilloma Virus (HPV) infection. HPV positive oropharyngeal cancer is often more radiosensitive and first line treatment includes either radiotherapy or surgical resection. Trials are ongoing to establish situations in which radiation doses can be reduced with the aim of reducing late tissue toxicity ("de-escalation trials") . We report a case in which a patient failed to complete his prescribed radiotherapy treatment, describe his clinical outcomes and the potential questions this situation raises. Method: In 2009 a male patient presented with a right T2N0MO P16 positive tonsillar squamous cell carcinoma. He was scheduled to complete a course of chemoradiotherapy. However, he was only able to complete a third of the radiotherapy course. Due to unresolved symptoms, he underwent a right transoral laser extended tonsillectomy, however this showed only fibrous tissue. Results: Despite not completing the radiotherapy course he has not experienced local recurrence of the tonsillar OPSCC 11 years post initial treatment. Conclusions: This case illustrates that some patients with HPV driven oropharyngeal cancer can have a clinically significant tumour response to markedly lower doses of radiotherapy than is currently recommended. Further randomized controlled trials are required to establish the optimum dose in the management of HPV driven oropharyngeal squamous cell cancer.